Academic Pressure and Student Unethical Behavior: An Empirical Study of the Use of Thesis Jockey Services - Fathoni, Achmad Robbi (Journal of Correctional Management, 2024)
The phenomenon of using thesis jockey services among students is increasingly widespread and has become a serious problem in higher education in Indonesia. This study aims to identify the factors that encourage students to use thesis jockey services and analyze its impact on the quality of higher education. The method used is a literature review encompassing various empirical studies related to this topic. The findings indicate that academic pressure, lack of time management skills, and low academic integrity are the main factors driving students to seek shortcuts through thesis jockey services. The use of these services negatively impacts students' academic skill development and damages the reputation of educational institutions. To address this issue, comprehensive strategies are needed, including strengthening supervision systems, enforcing sanctions, developing character education programs, and providing adequate academic support. Fenomena penggunaan jasa joki skripsi di kalangan mahasiswa semakin marak dan menjadi masalah serius dalam dunia pendidikan tinggi di Indonesia. Penelitian ini bertujuan untuk mengidentifikasi faktor-faktor yang mendorong mahasiswa menggunakan jasa joki skripsi serta menganalisis dampaknya terhadap kualitas pendidikan tinggi. Metode yang digunakan adalah tinjauan literatur yang mencakup berbagai studi empiris terkait topik ini. Hasil penelitian menunjukkan bahwa tekanan akademik, kurangnya keterampilan manajemen waktu, dan rendahnya integritas akademik merupakan faktor utama yang mendorong mahasiswa mencari jalan pintas melalui jasa joki skripsi. Penggunaan jasa ini berdampak negatif pada pengembangan keterampilan akademik mahasiswa dan merusak reputasi institusi pendidikan. Untuk mengatasi masalah ini, diperlukan strategi komprehensif yang meliputi penguatan sistem pengawasan, penegakan sanksi, pengembangan program pendidikan karakter, dan penyediaan dukungan akademik yang memadai.